On the development and evaluation of a serious game for forensic examination training - Drakou, Maria; Lanitis, Andreas (My University, 2016)
Training for forensic investigations is an important aspect of the overall training procedure in Police Academies around the world. However, the overall complexity of forensic examinations and the sensitive nature of data available in crime scenes limit the possibility of exposing police cadets in different types of real crime scenes. In this paper the plausibility of using dedicated computer games and Virtual Environments for forensic examination training is investigated in order to support the development of computer-based systems for training cadets to perform forensic examinations. This effort, that was carried out in cooperation with the local Police Authorities, involved the collection of information of procedures adopted during forensic investigations, the design and implementation of a computer game to support relevant educational activities and the evaluation phase where the end product was thoroughly evaluated. The results of the evaluation indicate that it is plausible to use dedicated computer games as part of training for forensic examinations.
Keywords: Forensic examination; Serious game; Virtual Reality